To Retrench or Invest? Evaluating the Turnaround and Recovery Strategies of Indonesia MNEs through Data Science Approaches - Willy Abdillah; Delly Nofiani; Maria Paramastri Hayuning Adi; Eka Marlina (Bright Publisher, 2024)
This study aims to investigate the turnaround and recovery strategies employed by Ecolab International Indonesia MNEs after facing significant financial decline caused by the COVID-19 pandemic. This research analyzed internal factors, external opportunities, and threats to define effective strategies using a multi-method approach. Qualitative interviews were conducted to identify key themes, supported by examining company publications, especially annual financial reports from 2018 to 2022, to understand economic trends before, during, and after the pandemic. Thematic analysis was utilized to analyze the results, involving coding interview transcripts using ATLAS.ti and validating these themes through member checking to ensure reliability. Our findings show that Ecolab's turnaround strategy (cost reduction, enhancing value in sustainability, restructuring leadership, and organizational culture) was essential in addressing immediate and long-term challenges. The recovery strategy (operational and financial strategies, strategic focus area, regulatory and market dynamics) helped the company navigate the pandemic's impact and its position for sustainable growth. This study breaks new ground by integrating sustainability into strategic frameworks, aligning with global trends. Offering fresh perspectives enhances the relevance and value of MNEs' corporate strategy research in emerging markets. Additionally, our findings provide actionable insights for other companies to effectively incorporate sustainable practices into their turnaround and recovery strategies, ensuring long-term growth and regulatory compliance.